Relations between the Russian Federation and the Republic of South Ossetia - Mansurov Timur Zufarovich, Viktoriya Aleksandrovna Pavlova, (Opción, 2019)
The purpose of the study is to identify the characteristics of relationship development between the Russian Federation and the Republic of South Ossetia after the armed conflict that occurred in 2008 via the system and institutional approaches as the research methodology. As a result, the analysis carried out in the article shows that the relations between Russia and South Ossetia are developing in a positive way. In conclusion, there will be a deepening of the integration process between the countries in question, periodically accompanied by minor contradictions and conflicts.